Interpretation of "Visio Smaragdina", a Poem of Juan Eduardo Cirlot, in Jesús Torres’ Composition «Proteus» (Castilla. Estudios de Literatura, 2020)
In 2004 Jesús Torres composed Proteus, a brief and highly symbolic work thought to be executed by a unique percussionist. Towards the end of the composition we can listen an astonishing poem of Juan Eduardo Cirlot titled Visio smaragdina. Besides the semantic of the colour and the idea of metamorphosis that overflies the composition, we can find a serial of key aspects related to Sufism. We will explore this last with the help of Henry Corbin’s ideas. In the folowing pages we will show the significances of both works -Cirlot’s poem and Torres’ piece- in relation with the contempary view of the world.
Keywords: Juan Eduardo Cirlot; Jesús Torres; 20th century Spanish Poetry; Contemporary music; contemporary music